Les partenariats public-privé pour développer le réseau routier national: Une perspective indienne - Gajendra Haldea (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2013)
– India's road network of over 4.1 million km is second largest in the world consisting of expressways, national highways, state highways, major district roads and other roads. These roads carry about 65 per cent of freight and 80 per cent of passenger traffic. National highways constitute only 1.7 per cent of the road network, but carry about 40 per cent of the total road traffic. Road Transport has emerged as the dominant segment in India's transportation sector with a share of 4.7% in India's GDP in 2009-10. The number of vehicles on Indian roads has been growing at an average pace of 10.16% per annum over the last five years. Hence, development of road network assumes paramount importance in the context of a rapidly growing economy.
Keywords: 330; Autobahn; Öffentlich-private Partnerschaft; Indien